Theoretical Outlines of Folklore and Naive, Snežana Šarančić Čutura, Folklorno u prostoru naivnog. Usmena književnost u kontekstu književnosti za decu, Sombor: Pedagoški fakultet, 2017. - Mitić, Kristina R. (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
Abstract in English is not available.